Characterization and quantification of microstructures of a fluorinated terpolymer by both homonuclear and heteronuclear two‐dimensional NMR spectroscopy. (17th October 2014) - Ok, Salim
<x xml:space="preserve">Abstract</x> Fluoropolymers are usually insoluble in organic solvents. Insolubility of fluoropolymers limits basic characterization such as microstructural investigations. In the family of fluoropolymers, terpolymer of tetrafluorethylene (TFE), hexafluoropropylene (HFP), and vinylidene fluoride (VDF), named THV is one of the newest members. There are nine grades of THV available. Among the nine grades, THV‐221 G is an ideal model polymer for basic characterization purposes. THV‐221 G is soluble in solvents such as acetone and ethyl acetate. In the current report, both homonuclear and heteronuclear 2D NMR experiments were employed in solution on THV‐221 G. The homonuclear gradient correlation spectroscopy NMR measurement revealed that THV has two adjacent TFE units in addition to TFE‐HFP sequence orders. The fraction of the microstructures is quantified by the analysis of 1D solution 19F NMR spectrum. Further, the gradient heteronuclear single quantum coherence experiment helped with the clarification of chemical environments of the units TFE, HFP, and VDF. The 1D solution 13C NMR spectrum was helpful in clarifying sequence assignments of VDF. It is concluded that THV is a random polymer with a limited fraction of TFE‐TFE and TFE‐HFP sequence orders in addition to head‐to‐tail polymerization of VDF unit. Copyright © 2014 John Wiley & Sons, Ltd.